Redesign Layout of the Hazardous Waste Storage Area for the Medical Device Manufacturing Industry - Firmansyah, Ferry; Farahdiba, Aulia Ulfah (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Hazardous waste is waste generated by a business or activity that has chemical, physical, or biological characteristics that pose a danger to human health and the environment. The medical device manufacturing industry generates hazardous waste, including used lubricating oil, used rags, product rejects, and fluorescent lamp electronic waste. This industry already has a hazardous waste storage facility that temporarily stores hazardous waste, but as the company grows, several new rooms or facilities will be needed to support the production process. Therefore, changes in waste production necessitate the redesign of the hazardous waste storage facility. The data collection method used primary data (field observations and interviews) and secondary data (Rintek Hazardous Waste Management and regulations applicable to hazardous waste management in Indonesia). Based on the findings of gaps and waste volume data, the number of containers was recalculated, and a space requirement analysis was carried out by grouping waste into compatible zones and ensuring physical separation. The selection of containers and packaging materials was adjusted to the waste's physical and chemical properties. The redesigned layout applies a separate block system based on a compatibility matrix so that incompatible waste is not stored side by side, with a safe distance of 60 cm in accordance with Minister of Environment and Forestry Regulation No. 6 of 2021. Contribution to Sustainable Development Goals (SDGs):SDG 3 – Good Health and Well-beingSDG 9 – Industry, Innovation, and InfrastructureSDG 13: Climate Action